Analiza wpływu innowacyjnego narzędzia na wspomaganie działalności firm z branży FMCG na rynku polskim - Przemysław Miller (Ekonomiczne Problemy Usług, 2016)
The following paper presents results of analyses of the use of an innovative tool on the Polish market to support the process of invoice pre-financing. The aim of this study is to verify the potential of this tool used by Polish companies in the FMCG branch. For this purpose, a study of the development of this financing instrument based on an analysis of research material and literature on the subject has been performed.